Control System of Parameters of the Azimuthal Module; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Plotnikova I. V. Inna Vasilievna; Galtseva (Gal’tseva) O. V. Olga Valerievna; Tchaikovskaya O. N.; Tchekarova S. A. (Technologies and equipment for their implementation, 2017)
Title screen